Translocation of wild Laysan Teal Anas laysanensis from Laysan Island to Midway Atoll: project update - Reynolds, Michelle H; Breeden Jr, James H; Klavitter, John L (Wildfowl, 2013)
The Laysan Teal Anas laysanensis is endemic to the Hawaiian Islands, where it has been restricted to Laysan Island over the last 150 years. Individuals of this endangered species have recently been translocated to the two largest islands that comprise Midway Atoll National Wildlife Refuge, to reduce the risk of the Laysan Teal becoming extinct. Post-release monitoring with the aid of radio-telemetry was conducted to determine the success of the reintroduction attempt during October 2004â€“2007. The population was found to have increased after three breeding seasons, from forty-two founders sourced directly from Laysan, to a population of â‰¥ 192 post- fledglings juveniles and adults.